Model Pemangku Kepentingan dalam Keberhasilan Proyek - Herry Pintardi Chandra; Indarto .; I Putu Artama Wiguna; Peter F. Kaming (Institute of Research and Community Outreach - Petra Christian University, 2011)
Stakeholder condition is particularly important to reach project success. The objective of this study is to investigate the stakeholder conditions which are suggested in three parts; stakeholder impact, stakeholder engagement, and stakeholder psychological empowerment on project success. The data obtained from a questionnaire survey administered to 197 respondents for initial research, 204 for main research, and 5 construction companies for validation research by using structural equation modeling (SEM) with program AMOS 16. The results indicated that stakeholder psychological empowerment applying of the ability to perform has a significant influence on project success measured by quality performance. On the other hand, stakeholder engagement reflected by engagement scope has no significant influence on project success